Open and Distance Learning Mode in Nepal: Practice and Challenges - Ghimire, Nani Babu (Sotang, Yearly Peer Reviewed Journal, 2020)
Open and distance learning (ODL) is accepted as an alternative mode of education which is defined as a new trend in instruction wherein the learner is geographically separate from the source can involve in learning process. This study presents a clear figure of the current practice and challenges of ODL for ensuring access to higher education in the context of Nepal. As qualitative study, narrative inquiry research design was exercised and four participants were selected purposively to extract their experiences, understanding and perception on ODL through semi structured interview. The interviews were transcribed and thematically analysed developing two global themes in relating to literature. The findings of the study suggested that the practice of open and distance learning mode in Nepal is not so developed and people are not satisfied with its provision. It is not adequately managed and also not in the access to the target groups because of highly prioritized formal education system. The lack of physical facilities, electricity supply, Information Communication Technology (ICT) devises, unavailability of capable expert, lacking strong commitment of the concerned agencies to provide quality assurance are its challenges.